Perancangan Sistem Informasi Geografis Pemetaan Lokasi Penghasil Kopi di Kabupaten Garut Menggunakan Rational Unified Process - Nashrulloh, Muhammad Rikza; Kurniadi, Dede; Maulana, Yusep; Muttaqin, Moch Riefky Chaerul (Institut Teknologi Garut, 2023)
Coffee is a popular drink nowadays because many people like it. However, farmers and coffee drinkers in Garut Regency face the problem of not having access to real-time information about the geographical location of coffee producers in the region. Therefore, this research aims to develop a Geographic Information System (GIS)-based system that can provide spatial information about coffee producing locations in Garut Regency more easily. The methodology used in this research is the Rational Unified Process (RUP) which consists of inception, elaboration and construction stages. In this stage, data modeling will be carried out using Unified Modeling Language (UML) and system testing using Black-Box Testing. The final result of this research is the success of developing a Geographic Information System (GIS) for mapping coffee producing locations in Garut Regency. This system can be accessed via the web and provides spatial information about the geographic location of coffee producers easily and accurately. Alpha testing using the black-box testing method has been carried out to test various features in the system. The test results show that all features in the system work well and as expected. This testing also helps identify and fix some potential issues before the system is fully rolled out. With this system, it is hoped that it can help increase efficiency in obtaining information about coffee producing locations in the region.